The influence of internal control on fraud prevention (Case study at Bank BRI of Cimahi City) - Rahadiyan Nugraha; Bunga Indah Bayunitri (Goodwood Publishing, 2020)
Purpose: The purpose of this research was to determine how much the influence of Internal Control against Fraud Prevention at Bank BRI of Cimahi City. Internal control is an interlocking set of activities that are carried out by the board of directors, management, and other personnel. It is designed to provide confidence in achieving certain goals within the organization. Fraud Prevention is a precautionary measure by creating policies, procedures, organization, control techniques, and employee participation. Research methodology: The research method used in this study was explanatory method. The number of samples in this study were 46 employees of Bank BRI of Cimahi City. The analytical method used in this study was Partial Hypothesis Test (T-Test) with significance level of 5%. The program used to analyze data was Statistical Package for Social Sciences (SPSS) Ver20.00. Result: According to this research, internal control has a significant effect on fraud prevention by 50.2% Limitation: This research only described Bank BRI of Cimahi City. Contribution: This study can be useful for students, banking employees, and future researchers. Keywords: Bank BRI of Cimahi City, Fraud prevention, Internal control